Top-down fragmentation of a warm dark matter filament - Knebe, A; Devriendt, J; Gibson, B; Silk, J (2003)
We present the first high-resolution N-body simulations of the fragmentation of dark matter filaments. Such fragmentation occurs in top-down scenarios of structure formation, when the dark matter is warm instead of cold. In a previous paper, we showed that warm dark matter (WDM) differs from the standard cold dark matter (CDM) mainly in the formation history and large-scale distribution of low-mass haloes, which form later and tend to be more clustered in WDM than in CDM universes, tracing the filamentary structures of the cosmic web more closely. Therefore, we focus our computational effort in this paper on one particular filament extracted from a WDM cosmological simulation and compare in detail its evolution to that of the same CDM filament. We find that the mass distribution of the haloes forming via fragmentation within the filament is broadly peaked around a Jeans mass of a few 109 M ⊙, corresponding to a gravitational instability of smooth regions with an overdensity contrast around 10 at these redshifts. Our results confirm that WDM filaments fragment and form gravitationally bound haloes in a top-down fashion, whereas CDM filaments are built bottom-up, thus demonstrating the impact of the nature of the dark matter on dwarf galaxy properties.